2003
DOI: 10.1038/sj.onc.1206589
|View full text |Cite
|
Sign up to set email alerts
|

Molecular processes of chromosome 9p21 deletions in human cancers

Abstract: Interstitial deletions of the chromosome 9p21 segment encoding the p16/CDKN2A tumor suppressor gene (i.e., 9p21 deletions) are frequently observed in a variety of human cancers. A majority of these deletions in lymphoid leukemia have been indicated to be mediated by illegitimate V(D)J recombination. In the present study, to elucidate the molecular processes of 9p21 deletions in nonlymphocytic malignancies, breakpoints for these deletions were analysed in 21 lung cancer cell lines and 32 nonlymphocytic cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 30 publications
8
65
0
Order By: Relevance
“…Therefore, the chromatin for the BCSs was thought to take a configuration(s) making them susceptible to digestion by DNA endonucleases such as restriction enzymes and RAG proteins. Breakpoints for 9p21 deletions in nonhematological malignancies were not mapped at specific DNA sequences (Florl and Schulz, 2003;Sasaki et al, 2003;Raschke et al, 2005). Therefore, genomic features enhancing DSBs were unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the chromatin for the BCSs was thought to take a configuration(s) making them susceptible to digestion by DNA endonucleases such as restriction enzymes and RAG proteins. Breakpoints for 9p21 deletions in nonhematological malignancies were not mapped at specific DNA sequences (Florl and Schulz, 2003;Sasaki et al, 2003;Raschke et al, 2005). Therefore, genomic features enhancing DSBs were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated that DSBs triggering deletions in lymphoid leukemia are produced by the RAG complex, a DNA endonuclease used for V(D)J recombination, while those in other cancers are produced at unspecific sites by as yet unidentified factors (Kitagawa et al, 2002;Sasaki et al, 2003). Thus, the distributions were analysed not only in total but also after dividing into lymphoid leukemia and other cancers.…”
Section: à2mentioning
confidence: 99%
See 3 more Smart Citations